Hubungan Kepercayaan Diri dengan Kemandirian pada Pasien Kanker Payudara yang Menjalani Kemoterapi - Trianadewi, I Gusti Agung Indah; Suratiah, Suratiah; Surinati, Dewa Ayu Ketut; Hartati, Ni Nyoman; Ribek, Nyoman (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2024)
The most common cause of death among women worldwide is breast cancer, which is the most commonly diagnosed type of cancer. Breast cancer is a condition where cells lose control of their normal activity, resulting in abnormal growth. One of the treatments for breast cancer is chemotherapy. Chemotherapy can cause side effects, which can have an impact on the fulfillment of daily activities that cause the inability to perform self-care independently. The purpose of this study was to determine the relationship between self-confidence and independence in breast cancer patients undergoing chemotherapy at Bali Mandara Hospital in 2024. The type of research used is correlational with a cross-sectional approach. Sampling using purposive sampling technique as many as 79 people. Data collection instruments used a self-confidence questionnaire and a Barthel index questionnaire. The results of the study of self-confidence of breast cancer patients undergoing chemotherapy in the very confident category 55.7%, the independence of breast cancer patients undergoing chemotherapy in the moderate category 45.6%. The hypothesis test used is the spearman rank test with a p-value = 0.000 α (0.05), it can be concluded that there is a relationship between self-confidence and independence in breast cancer patients undergoing chemotherapy.